Flowering, fruit set and breeding systems of Habenaria janellehayneana and H. rhodocheila in Phu Hin Rong Kla National Park, Thailand (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Thummavonsa T, Musimun C, Watthana S, Muangsan N. 2025. Flowering, fruit set and breeding systems of Habenaria janellehayneana and H. rhodocheila in Phu Hin Rong Kla National Park, Thailand. Biodiversitas 26: 3246-3251. Reproductive biology studies are important information for orchids conservation in natural habitats, especially ones which have high potential for economic use. Over-collection is a main threat of orchid species with economic value. Moreover, the reduction of the habitat and climate change may result in population decline or extinction. Fruit set data is a preliminary evaluating the population survival, valuable for population conservation. This study aimed to examine flowering, natural fruit set and breeding systems of Habenaria janellehayneana and H. rhodocheila, attractive terrestrial orchids for pot plants, in Phu Hin Rong Kla National Park, Phitsanulok Province, Northern Thailand to collect basic information for in situ conservation. Two studied plots, 50x50 m plots of each species, were established to investigate the flowering and fruit set. Three experiments of hand-pollination, untouched, self- and cross-pollination were performed to compare with natural pollination to determine the breeding systems. Leaf length and shoot length showed no correlation with fruit set (r
Keywords: Breeding systems, fruit and seed production, Habenaria, in situ conservation, terrestrial orchid